Conversion of Conventional Cooperatives to Sharia Affected by Cooperative Skills, Discipline and Work Environment - Nasfi, Nasfi; Prawira, Adi; Yunimar; Lutfi, Ahmad; Aziz, Zakaria (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This study aims to determine the conversion conventional cooperatives into sharia cooperatives are influenced by skills, discipline and cooperative environment. About 10 cooperatives as well as research samples with 3 respondents per cooperative, so that a total of 30 respondents. Quantitative research method with 30 respondents managing cooperatives (chairman, secretary and treasurer), from 10 cooperatives requested by the Department of Industry and Trade and SMEs of Solok City. The sampling technique used was non-probability sampling with saturated samples or the census method. Collecting data in this study by distributing questionnaires to all respondents. The analytical method used in this study uses multiple linear regression analysis with the help of the SPSS program. Found there is an influence between the variables of management skills, management work discipline, and cooperative work environment simultaneously on the work productivity of managers. Sharia management skills, sharia work discipline and cooperative environment in Solok City have a positive and significant effect on the work productivity.